Designing healthy foods – A dietetic marketing perspective. (1st October 2018) - Sandvik, Pernilla
Research in natural sciences often demonstrates health potential of specific foods. However, for these foods to have a beneficial effect in reality, they also need to be available, chosen, liked and eaten by consumers. To find strategies to enable an increased consumption of foods with potential health benefits, a perspective described as dietetic marketing will be elaborated upon. This is done by using the example of rye bread as a potential health beneficial component in the Swedish diet. Several potential health benefits have been shown for rye, but less research has been focused on bread from a consumer perspective. Dietetic marketing draws upon ideas from social marketing but focuses specifically on a food with potential health benefits. Here, consumers are thought to more easily adopt a behaviour if they receive benefits they consider valuable or if relevant barriers are removed. Food quality is a useful concept in identifying barriers to and opportunities for consumption. Objective quality represents, e.g., what is described as healthy and recommended by authorities as well as what is made available to consumers by food industry. Subjective quality is related to consumer perceptions of these qualities. Taste is a crucial quality criterion for consumers' evaluation of food products. Sensory analysis is therefore used as a key methodology to bridge the gap between the product and the person. In the case of healthier rye breads, the taste was shown to be a major barrier for consumption among Swedish consumers. With the aim to increase consumption of foods with potential health benefits, a dietetic marketing perspective gives interdisciplinary insights into how industry may design products and communication in line with consumer perceptions and preferences as well as how authorities may design recommendations and guidelines to aid consumers in their food choice and guide industry in product development.